The Semiotic Landscape of Maritime Resilience: A Peircean Analysis of the Nandong Syair Perahu in Simeulue Island, Aceh - Rahmi Putri Ramadani; Zulkhairi Zulkhairi; Putra Hidayatullah; Hajah Norhayati Binti Haji Abd Karim (Winaya Inspirasi Nusantara Foundation, 2027)
The vast Indonesian archipelago, local oral traditions serve as crucial cognitive frameworks for preserving ancestral ecological wisdom and managing socio-environmental risks. On the isolated island of Simeulue, the Nandong oral performance represents a vital cultural institution, yet its specialized maritime sub-genre, the Syair Perahu (Boat Poem), has remained largely unexamined at a fine level of linguistic granularity. This study aims to deconstruct the semiotic mechanisms of the Syair Perahu to understand how physical maritime elements and natural phenomena are assigned practical, survival-based cultural meanings. Using a descriptive qualitative ethnographic design, this research systematically analyzes the transcribed oral verses of the poem through the application of Charles Sanders Peirce’s triadic semiotic model (Representamen, Object, and Interpretant). Primary data were gathered through participant observation and in-depth interviews with three respected seniman tutur (oral artists) in Simeulue. The findings demonstrate that the Syair Perahu operates as an active, secular cognitive map and safety manual. Specific linguistic signs, such as local timber (kayu kapo-kapo) and hydrodynamic forms (ransung salodang), are indexically linked to structural durability and strict passenger capacity limits. Similarly, environmental hazards like the angin sumadin and lauik api function as indexical warnings that trigger social safety rules and spiritual invocation, while the capturing of samen-samen fish symbolizes economic self-sufficiency. Ultimately, this study implies that endangered oral literatures are sophisticated educational systems of maritime resilience, highlighting the urgent need for regional heritage bodies to integrate ancestral ecological wisdom into modern coastal safety policies.